The Structuring of Sage (Salvia officinalis L.) Extract-Incorporating Edible Zein-Based Materials with Antioxidant and Antibacterial Functionality by Solvent Casting versus Electrospinning - Ana Salević; Dušica Stojanović; Steva Lević; Milena Pantić; Verica Đorđević; Radojica Pešić; Branko Bugarski; Vladimir Pavlović; Petar Uskoković; Viktor Nedović (Foods, 2022)
In this study, in order to develop zein-based, edible, functional food-contact materials in different forms incorporating sage extract (10, 20, and 30%), solvent casting and electrospinning were employed. The study aimed to assess the effects of the applied techniques and the extract’s incorporation on the materials’ properties. The solvent casting generated continuous and compact films, where the extract’s incorporation provided more homogenous surfaces. The electrospinning resulted in non-woven mats composed of ribbon-like fibers in the range of 1.275–1.829 µm, while the extract’s incorporation provided thinner and branched fibers. The results indicated the compatibility between the materials’ constituents, and efficient and homogenous extract incorporation within the zein matrices, with more probable interactions occurring during the solvent casting. All of the formulations had a high dry matter content, whereas the mats and the formulations incorporating the extract had higher solubility and swelling in water. The films and mats presented similar DPPH• and ABTS•+ radical scavenging abilities, while the influence on Staphylococcus aureus and Salmonella enterica subsp. enterica serovar Typhimurium bacteria, and the growth inhibition, were complex. The antioxidant and antibacterial activity of the materials were more potent after the extract’s incorporation. Overall, the results highlight the potential of the developed edible materials for use as food-contact materials with active/bioactive functionality.